Discovery of novel 5-fluoro-N2, N4-diphenylpyrimidine-2, 4-diamines as potent inhibitors against CDK2 and CDK9. Issue 3 (9th December 2014) - Gao, Jiadi; Fang, Cheng; Xiao, Zhiyan; Huang, Li; Chen, Chin-Ho; Wang, Li-Ting; Lee, Kuo-Hsiung
Abstract : Novel 5-fluoro-pyrimidine derivatives have been designed, synthesized and evaluated as potential CDK inhibitors as well as antitumor and anti-HIV agents. Abstract : Based on a 3D-QSAR pharmacophore derived from a diverse set of known cyclin-dependent kinase 9 (CDK9) inhibitors and a composite pharmacophore extracted from the complex structure of flavopiridol (FVP)-CDK9, thirty novel 5-fluoro- N 2, N 4 -diphenylpyrimidine-2, 4-diamine derivatives were designed and synthesized. Initial tests against four tumor cell lines with the sulforhodamine B (SRB) assay identified a series of potent compounds with GI50 values at a lower micromolar or submicromolar level. Most of the highly cytotoxic compounds exhibited potent inhibitory activities against both CDK2/cyclin E1 and CDK9/cyclin T1. Notably, inhibitions against the two enzymes were generally correlated well with the cytotoxicity of these compounds. Appreciable inhibition was also observed for selected compounds in the anti-HIV-1 assay. Docking studies on compounds6d and9g provided conducive clues to further structural optimization.